Interaction Between 2 Nutraceutical Treatments and Host Immune Status in the Pediatric Critical Illness Stress‐Induced Immune Suppression Comparative Effectiveness Trial. (22nd September 2016) - Carcillo, Joseph A.; Dean, J. Michael; Holubkov, Richard; Berger, John; Meert, Kathleen L.; Anand, Kanwaljeet J. S.; Zimmerman, Jerry J.; Newth, Christopher J. L.; Harrison, Rick; Burr, Jeri; Willson, Douglas F.; Nicholson, Carol; et al.
Abstract : Background and aims: The pediatric Critical Illness Stress‐induced Immune Suppression (CRISIS) trial compared the effectiveness of 2 nutraceutical supplementation strategies and found no difference in the development of nosocomial infection and sepsis in the overall population. We performed an exploratory post hoc analysis of interaction between nutraceutical treatments and host immune status related to the development of nosocomial infection/sepsis. Methods: Children from the CRISIS trial were analyzed according to 3 admission immune status categories marked by decreasing immune competence: immune competent without lymphopenia, immune competent with lymphopenia, and previously immunocompromised. The comparative effectiveness of the 2 treatments was analyzed for interaction with immune status category. Results: There were 134 immune‐competent children without lymphopenia, 79 previously immune‐competent children with lymphopenia, and 27 immunocompromised children who received 1 of the 2 treatments. A significant interaction was found between treatment arms and immune status on the time to development of nosocomial infection and sepsis ( P < .05) and on the rate of nosocomial infection and sepsis per 100 patient days ( P < .05). Whey protein treatment protected immune‐competent patients without lymphopenia from infection and sepsis, both nutraceutical strategies were equivalent in immune‐competent patients with lymphopenia, and zinc, selenium, glutamine, and metoclopramide treatment protected immunocompromised patients from infection and sepsis. Conclusions: The science of immune nutrition is more complex than previously thought. Future trial design should consider immune status at the time of trial entry because differential effects of nutraceuticals may be related to this patient characteristic.